2022
DOI: 10.3390/ijerph19074284
|View full text |Cite
|
Sign up to set email alerts
|

Benefit Finding and Related Factors of Patients with Early-Stage Cancer in China

Abstract: (1) Background: Although the research on benefit finding (BF) in China has increased in recent years, it remains in its infancy. Few previous studies have focused on early-stage cancer patients. Therefore, this research study aimed to explore BF and its influencing factors for early-stage cancer patients in China. (2) Methods: From April to August 2019, 319 patients with early-stage cancer in the treatment period were selected by the convenience sampling method and evaluated using the Benefit Finding of Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…On the other hand, it helps to guide healthy behavior and improve the perception of social support, thus promoting the rehabilitation of the disease. [64] Recent benefit-finding studies have focused on various cancers and diseases with a long-term burden, such as rheumatoid arthritis and type 1 diabetes. [65,66] Endoscopic screening is already widely performed in China, followed by removing polyps that can interrupt the progression of adenomas to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it helps to guide healthy behavior and improve the perception of social support, thus promoting the rehabilitation of the disease. [64] Recent benefit-finding studies have focused on various cancers and diseases with a long-term burden, such as rheumatoid arthritis and type 1 diabetes. [65,66] Endoscopic screening is already widely performed in China, followed by removing polyps that can interrupt the progression of adenomas to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who use accept-resignation as the coping strategy might believe that their illness cannot be resolved, and when confronting it, they are unable to take any action, with an increased feeling of helplessness [ 29 ]. Another possible explanation is that acceptance-resignation might put patients in a negative mood in the long run, affect their initiative [ 30 ], thus reduce their positive psychological changes-PTG. Therefore, it is suggested that medical staff strengthen the psychological guidance of adult SLE patients and guide them to adopt positive coping styles to enhance PTG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they could enhance a better coping strategy through this group-based intervention. The opportunities to think about how to extend good social support, as well as to improve coping strategy seemed to be effective to strengthen their benefit finding [ 7 , 10 , 33 , 34 ]. The process of benefit finding may be naturally experienced by themselves without any specific intervention as observed in previous studies [ 7 ], because the control group showed slight and gradual progress in benefit finding.…”
Section: Discussionmentioning
confidence: 99%
“…While benefit finding and personal recovery have similar perspectives, benefit finding is explained as a phenomenon relevant to coping, which can be enhanced in people with chronic illness, such as cancer [ 10 , 11 ]. On the other hand, personal recovery indicates a subjective process of their own lives with mental illness.…”
Section: Introductionmentioning
confidence: 99%